2022
DOI: 10.3892/etm.2022.11235
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of nomifensine using ionizing radiation and exploration of its anticancer effects in MCF‑7 cells

Abstract: Breast cancer is one of the most challenging diseases to treat in humans worldwide. There are several alternatives in treating this life-threatening disease; however, chemoresistance is probably the biggest obstacle to the treatment of breast cancer. It may be essential to develop a therapeutic candidate material with less reversible effects and high treatment efficiency to solve this problem. The present study applied an ionizing radiation approach employing nomifensine (NF) to transform its chemical characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Among these derivatives, it was found that hydroxylation at the C-11 position of HBPA conferred the most potent inhibitory activity against the activation of pro-inflammatory mediators ( Table I ). Comparatively, the simple pyridine amide isonicotinamide ( 7 ) was characterized by relatively lower inhibitory activity against the production of both NO and PGE 2 in RAW 264.7 macrophages ( Table I ). Consistently, in canine DH82 macrophages, the hydroxyl-substituted benzylpropanamide derivative was established have the most potent inhibitory activity against the production of NO and PGE 2 , with IC 50 values of 57.5±0.6 and 49.4±0.4 µM, respectively ( Table I ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these derivatives, it was found that hydroxylation at the C-11 position of HBPA conferred the most potent inhibitory activity against the activation of pro-inflammatory mediators ( Table I ). Comparatively, the simple pyridine amide isonicotinamide ( 7 ) was characterized by relatively lower inhibitory activity against the production of both NO and PGE 2 in RAW 264.7 macrophages ( Table I ). Consistently, in canine DH82 macrophages, the hydroxyl-substituted benzylpropanamide derivative was established have the most potent inhibitory activity against the production of NO and PGE 2 , with IC 50 values of 57.5±0.6 and 49.4±0.4 µM, respectively ( Table I ).…”
Section: Resultsmentioning
confidence: 99%
“…of hydrazine-based nomifensine has been demonstrated to enhance the anticancer effects of this drug in treated breast cancer cells (7). Radiolytic radicals are powerful modifying agents that can initiate a range of modification reactions in lead compounds during irradiation (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, chrysin and luteolin showed improved anti-in ammatory activities in vitro and in vivo induced by γ-irradiation, and the chemical structure of hydroxyalkyl-substituted compounds was identi ed 12,21 . In addition, radiolytic transformation of alkaloids and steroids showed potent enhanced anti-cancer effects in melanoma, breast, liver, and lung cancer 11,[22][23][24][25] .…”
Section: Resultsmentioning
confidence: 99%
“…Gamma irradiation has received wide attention owing to its potential to decrease the toxicity of alkaloids, steroids, and avonoids and increase the biological capacities of these compounds 10,11 . Recently, the anti-depressant drug nomifensine (Merital®) was reported to effectively improve the anti-cancer properties in breast cancer cells after exposed to ionizing radiation 12 .…”
Section: Introductionmentioning
confidence: 99%